Nanocomposite polymeric materials with 3D graphene-based architectures: from design strategies to tailored properties and potential applications. (February 2019) - Salzano de Luna, M.; Wang, Y.; Zhai, T.; Verdolotti, L.; Buonocore, G.G.; Lavorgna, M.; Xia, H.
Graphical abstract: Abstract: In the last decade, a great deal of research has been devoted to the design and development of graphene-based polymer nanocomposites characterized by a prescribed arrangement of the graphene-based nanosheets into spatially segregated 3D architectures. The formation of a continuous filler network obtained by confining the nanosheets into a constrained volume of the polymeric matrix is particularly attractive from a technological point of view. The preparation of segregated 3D graphene-based architectures facilitates the proper tailoring of the overall performance of the resulting polymer nanocomposites, providing significant improvements in terms of structural (i.e., mechanical properties) and functional (electrical properties, sensing ability, and adsorption/absorption capacity) features. This review focuses on polymer-based nanocomposites in two categories, namely bulk and porous (foam and aerogels) systems. These all share the common distinctive feature that relies on the peculiar arrangement of the graphene-based nanosheets in the form of a segregated yet continuous 3D assembly. For each class of materials, the main preparation strategies are presented and the resulting structure-property correlations are highlighted and discussed, together with the technological implications, and possible future directions.